Pinocembrin ameliorates atrial fibrillation susceptibility in rats with anxiety disorder induced by empty bottle stimulation - Ran, Qian; Zhang, Cui; Wan, Weiguo; Ye, Tianxin; Zou, Ying; Liu, Zhangchi; Yu, Yi; Zhang, Junhua; Shen, Bo; Yang, Bo (Frontiers in Pharmacology, 2022)
Background: Anxiety disorder (AD) is the most common mental disorder, which is closely related to atrial fibrillation (AF) and is considered to be a trigger of AF. Pinocembrin has been demonstrated to perform a variety of neurological and cardiac protective effects through its anti-inflammatory and antioxidant activities. The current research aims to explore the antiarrhythmic effect of pinocembrin in anxiety disorder rats and its underlying mechanisms. Methods: 60 male Sprague-Dawley rats were distributed into four groups: CTL group: control rats + saline; CTP group: control rats + pinocembrin; AD group: anxiety disorder rats + saline; ADP group: anxiety disorder rats + pinocembrin. Empty bottle stimulation was conducted to induce anxiety disorder in rats for three weeks, and pinocembrin was injected through the tail vein for the last two weeks. Behavioral measurements, in vitro electrophysiological studies, biochemical assays, ELISA, Western blot and histological studies were performed to assess the efficacy of pinocembrin. In addition, HL-1 atrial cells were cultured in vitro to further verify the potential mechanism of pinocembrin. Results: After three weeks of empty bottle stimulation, pinocembrin significantly improved the exploration behaviors in anxiety disorder rats. Pinocembrin alleviated electrophysiological remodeling in anxiety disorder rats, including shortening the action potential duration (APD), prolonging the effective refractory period (ERP), increasing the expression of Kv1.5, Kv4.2 and Kv4.3, decreasing the expression of Cav1.2, and ultimately reducing the AF susceptibility. These effects may be attributed to the amelioration of autonomic remodeling and structural remodeling by pinocembrin, as well as the inhibition of oxidative stress with upregulation of the nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) pathway. Conclusions: Pinocembrin can reduce AF susceptibility in anxiety disorder rats induced by empty bottle stimulation, with the inhibition of autonomic remodeling, structural remodeling, and oxidative stress. Therefore, pinocembrin is a promising treatment for AF in patients with anxiety disorder.